Geopolitics of New Independent States of Central Asia in post-Soviet period - Levyk, Bogdan (Skhid, 2014)
The conditions for development of a regional system of national security in Central Asia in the post-Soviet period are reviewed in a new geopolitical context. The emergence in the region of new political actors of the first echelon - the USA, the European Union and the People’s Republic of China as well as the second echelon - Turkey, the Islamic republic of Iran, India and Pakistan is emphasized. The role of the above countries in ensuring political and economic security is traced. The regional integration situation is analyzed. Available regional threats, some of them of global nature, are looked into, their characteristic features described for each New Independent State. Interstate conflicts and their resolution potentiality in the current situation are investigated. The unity of the region in combatting international terrorism and extremism is pointed out. Regional threats which endanger the West are identified. Special attention is given to politicization of Islam, radical fundamentalism and their belligerent manifestations which took place in Central Asia. The membership of Central Asian countries in such security-focused interstate organizations as the Collective Security Treaty Organization and the Shanghai Cooperation Organization as well as relations with the UN and the NATO are laid stress on. A great military and technical dependence of the armed forces of Central Asian countries on the Russian factor is pointed out. Some facts of the geopolitical confrontation between Russia, the EU, the USA and China are referred to. Conclusions are drawn as to incapability of countries of the Central Asian region to stand up to current geopolitical challenges on their own and the lack of a regional security system. The necessity of multi-vector foreign policy as a form of guarantee against external aggression is brought into focus.